Assessment of area specific mineral mixture supplementation on growth and biochemical profile of Jersey crossbred heifers - Kondiba, MA; ., Vipin; Mandal, A; Karunakaran, M (Indian Journal of Dairy Science, 2022)
The present experiment was conducted to assess the effect of area specific mineral mixture (ASMM) supplementation on growth, onset of puberty, blood biochemical and hormonal profiles in Jersey crossbred heifers. Crossbred heifers (n=12) were allocated into two groups (6 in each) namely, control (T0) and treatment (T1) and fed without ASSM and with 30 g of ASMM/heifer/day for a period of four months. In the present study, mean of total body weight gain (42± 4.82 vs. 58.08± 6.42kg) and average daily gain (0.367 ± 0.07 vs. 0.480 ± 0.05 kg/d), plasma calcium (9.63 ± 0.57 vs. 9.85 ± 0.53 mg/dl), phosphorus (5.59 ± 0.33 vs. 5.88 ± 0.35 mg/dl), copper (0.56 ± 0.02 vs. 0.71 ± 0.02 ppm), zinc (0.59 ± 0.01 vs. 0.70 ± 0.02 ppm) and progesterone (0.67 ± 0.02 vs. 0.93 ± 0.06 ng/ml) were significantly lower (P0.05) between groups. Significantly (P